The hydration status of young female elite soccer players during an official tournament - Chapelle, L.; Tassignon, B.; Aerenhouts, D.; Mullie, P.; Clarys, P. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The hydration status of elite female soccer players is a concern, especially during high-volume training periods or tournaments. Furthermore, scientific literature on this topic is scarce to non-existent. Therefore, the primary aim of this study was to evaluate the hydration status in elite youth female soccer players during an official tournament. The secondary aim was to identify a possible relationship between pre-training hydration status and fluid intake.